Pelatihan Flowgorithm untuk Meningkatkan Kemampuan Dasar Pemrograman Siswa SMK Negeri 1 Pangkalan Kerinci - Riyanto Riyanto; Amir, Faisal; Fadilillah, Fadli; Oriyasmi, Fadhilah; Rozi, Fazrol; Laksono, Dedi Tri; Efendi, Novi (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The rapid development of digital technology requires vocational high school (SMK) students to have strong basic programming skills, yet algorithmic logic remains a major challenge. This study aims to enhance students’ understanding of basic programming through Flowgorithm training. The training was conducted face-to-face using demonstration and hands-on practice methods involving 32 eleventh-grade students of Software Engineering at SMK Negeri 1 Pangkalan Kerinci. Evaluation results show that most participants agreed the material met their needs and expectations, was engaging and easy to understand, and improved their programming logic skills. The study concludes that Flowgorithm is effective as a visual tool for programming logic. Its implication suggests similar training models can be applied in other vocational schools to strengthen students’ algorithmic thinking foundation.